Policies for Healthy Ageing An Overview - Oxley, Howard (OECD Health Working Papers, 2009)
This paper reviews policies in the area of healthy ageing. With the ageing of OECD countries' population over coming decades, maintaining health in old age will become increasingly important. Successful policies in this area can increase the potential labour force and the supply of non-market services to others. They can also delay the need for longer-term care for the elderly. A first section briefly defines what is meant by healthy ageing and discusses similar concepts - such as "active ageing". The paper then groups policies into four different types and within each, it describes the range of individual types of programmes that can be brought to bear to enhance improved health of the elderly. A key policy issue in this area concerns whether such programmes have a positive effect on health outcomes and whether they are costeffective